Cross-Border Co-operation in the Border Region of the Southern Great Plain of Hungary - Nagy, Imre (Discussion Papers, 2012)
Border regions have been the topic of research for over one decade. Now that borders are open in every direction, studying the border regions of the Southern Great Plain, we try to find possible areas of joint development. What we are experiencing in both the Yugoslavian and Romanian border regions foreshadows the problems of social, political and regional (development) transition, which is different and rather bumpy in either country. With the commencement of EU ac¬cession, cross-border co-operation as top priority and the establishment of the Danube-Körös-Maros-Tisza Euroregion, studies dealing with this border region either directly or indirectly started cropping up. The change of regime taking place almost simultaneously in Romania and Hungary has resulted in burgeoning Romanian-Hungarian relations. Initial relief has turned into commercial and (cross-border) economic co-operation still in embryo. Fast opening following the years of oppression has also been beneficial to both culture and science. Those living in the border regions have also forged closer links with one another as a result of daily contact and economic growth. Quite a few geographers, sociologists and economists have evaluated the proc¬esses in this region. The present study, after reviewing the history of border formation, attempts to define the term “border region” and presents the general characteristics of border regions. A major section of the study is devoted to the co-operation along the border between the South Plain and the border-zone regions of the neighbouring countries. In the final sections, the author presents the Danube-Körös-Maros-Tisza Euroregion and its role in the development of border zone relations and defines possible directions of future co-operation as carriers of effective area development.